English-Indonesian Translation Methods in the Story of “Malin Kundang” - Algrin Hayadi; Ira Maisarah; Seth Soy (English Education : English Journal for Teaching and Learning, 2022)
Abstract           This research contains an analysis of the methods in translation used in the short story  "Malin Kundang” by Dian K. the writers of the book and the writers derived the method theory from Newmark's view, she listed 8 methods in translation that can be used by all translators how to translate from English (SL) to Indonesian (TL) well and take into consideration to Malin Kundang story. In addition, the writers analyzed the reading text as data in this research by using the Qualitative descriptive Method. The writers make a comparison between the source language text ( SL) and the target language text ( TL) based on the theory of translation method by Peter Newmark and Baker's approach as well from the analysis the writers can explain the translation methods and the equivalent meanings of the translation. In the conclusion, the researcher finds 7 methods used in Malin Kundang's short story by the author. Besides, the researcher finds the equivalent meaning of translation in Malin Kundang's story as well since he also analyzed the equivalent, Which is textual equivalence. It is essential in replacing the message from one language ( SL) with another language (TL) to make the reader understand the reading text well. Keywords: Translation, Translation Method, Translation Equivalence, Short Story